Hubungan kepimpinan servant dengan keyakinan dan komitmen guru terhadap guru besar - Linggoh @ Lingoh, Anak Utan (2017)
It was said that teachers’commitment has strong relationship with the leadership styles and teachers’confidence (trust) toward the headmasters. The purpose of this study was to examine the significant relationship between the practice of servant leadership of the headmasters and teachers’commitment. It also attempted to determine the role of confidence (trust) as a mediator between the variables. This study employed quantitative technique by using questionnaires to collect the data from the respondents. There were 310 teachers from 93 primary schools in Betong Division participated in this survey. The instruments, Organizational Leadership Assessment (OLA) developed by Laub (1999) was used to measure the practice of servant leadership of the headmasters, Faculty Trust Scale developed by Tschannen-Moran & Hoy (2003) was used to measure teachers’confidence (trust) toward the headmasters while TCM Employee Commitment Survey developed by Meyer and Allen (2004) was used to measure teachers’ commitment toward the headmaster. The findings indicated that the practice of servant leadership of the headmasters and the teachers’ confidence (trust) toward the headmasters predicted and correlated significantly with teachers’ commitment toward the headmasters. The finding also showed that there were no significant differences between teachers’ level of commitment toward the headmasters based on demographic factors such as the level of education and age except teaching experience. The results from the regression analyses indicated that teachers’ confidence (trust) toward the headmasters did not served as a mediator between servant leadership of the headmaster and teachers’ commitment toward the headmasters. The servant leadership of the headmasters itself was found had a direct impact on teachers’ commitment toward the headmasters. Therefore, the headmasters should adopt servant leadership style in order to obtain confidence (trust) from the teachers and make them more committed toward the school. Beside that, it was suggested that the training provider like Ministry of Education, State Education Department and District Education Department to organize special course in servant leadership for the school leaders so that it will help them to understand this leadership style better. As a conclusion, this study has produced a significant theoretical frame that shows the contributions of servant leadership and teachers’ confidence (trust) toward teachers’ commitment to their headmasters.